Флористичні особливості Андрашівського озера (Закарпатська рівнина) - Фельбаба-Клушина, Л.М. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Приведены результаты исследования флоры Андрашивского озера. Проанализирована типологическая структура флоры. Особое внимание уделено третичному реликту Trapa natans L., для охраны которого предложено создать заказник государственного значения. The results of the study of the Andrash lake flora are presented. The typological structure of this flora is analized. The tertiar relict Trapa natans L. is discussed in details, and we proposed to arrange the state reserve to protect this species.